Joint scheduling of jobs and Preventive Maintenance operations in the flowshop sequencing problem: a resolution with sequential and integrated strategies. (6th January 2011) - Benbouzid-Sitayeb, Fatima; Guebli, Sid Ali; Bessadi, Yassine; Varnier, Christophe; , Noureddine Zerhouni
This paper presents a comparative study on joint production and Preventive Maintenance (PM) scheduling according to the most interesting joint scheduling strategies: sequential and integrated ones regarding Flow Shop Problems (FSPs). For each strategy, we present three heuristics: Genetic Algorithms (GAs), Taboo Search (TS) and NEH heuristic. The proposed heuristics have been applied to non-standard test problems, which represent joint production and maintenance benchmark flowshop scheduling problems taken from Benbouzid et al. (2003). A comparison of the solutions yielded by the heuristics developed in this paper with the heuristic solutions given by Taillard (1993) is undertaken with respect to the minimisation of performance loss after maintenance insertion. The comparison shows that the proposed integrated GAs are clearly superior to all the analysed algorithms.